Pengaruh Lingkungan Kerja, Budaya Kolaboratif, dan Kepuasan Kerja terhadap Turnover Intention pada PT Graha Megatama Indonesia selama Pandemi Covid-19 - Sintya Dwi Oktavia; Syarif Ali (Owner : Riset dan Jurnal Akuntansi, 2022)
This study is a quantitative research conducted with the purpose to know and prove the influence of the work environment, collaborative culture, and job satisfaction on turnover intention. The study object is the employees of PT Graha Megatama Indonesia. In this study, data were collected by distributing questionnaires via google form to 37 employees. The sampling method used in this research was a saturated sample technique, which consisted of 37 employees. The analysis in this study uses SmartPLS 3.0. The results indicate that: 1) the work environment has a negative and significant effect on turnover intention; 2) collaborative culture has a negative and significant effect on turnover intention; 3) job satisfaction has a significant negative effect on turnover intention; 4) work environment, collaborative culture, and job satisfaction simultaneously have a significant effect on turnover intention.